IMPROVING THE STUDENTS’ SPEAKING ACHIEVEMENT THROUGH ANDROID APPLICATION TFLAT ENGLISH TO THE 12th GRADE STUDENTS OF SMA NEGERI 1 PEUSANGAN SIBLAH KRUENG - Furqan, M furqan (Journal of English Education and Social Science, 2022)
ABSTRACT This research entitled is “Improving the Students Speaking Achievement Through Android Application TFlat English to The 12th Grade Students of SMA Negeri 1 Peusangan Siblah Krueng (a Collaborative Classroom Action Research). The researcher raised the problems of this research, namely: the first, how does the android application TFlat English improve the students speaking achievement? And the second, how do students respond to the implementation of the android application TFlat English at SMA Negeri 1 Peusangan Siblah Krueng?. The purpose of this study is to seen the improvement and students response to the application of the android application TFlat English as a medium for learning Speaking Achievement. The method used in this research is Collaborative Classroom Action Research. The researcher collaborated with teacher at SMA Negeri 1 Peusangan Siblah Krueng. The instruments used in this research are test, observation checklist and questionnaire. It can be seen that the mean score of the students' speaking test in the first cycle was 51.79% and in the second cycle it increased to 73.47%. The mean score of the first cycle of students’ observations was 56.6% while in the second cycle was 86.4%. The students’ response to the application of the TFlat English got an mean score of 83.95. These results indicate that the application of the TFlat English application in improving students' speaking achievement its good results and a satisfactory response. Thus this research is said to be successful.